Burden of Behavioral Health Comorbidities on Outpatient Health Care Utilization by Active Duty Service Members With a First Documented mTBI. (25th January 2021) - Kasuske, Lalon M; Hoover, Peter; Wu, Tim; French, Louis M; Caban, Jesus J
ABSTRACT: Objective: More than 280, 000 Active Duty Service Members (ADSMs) sustained a mild traumatic brain injury (mTBI) between 2000 and 2019 (Q3). Previous studies of veterans have shown higher utilization of outpatient health clinics by veterans diagnosed with mTBI. Additionally, veterans with mTBI and comorbid behavioral health (BH) conditions such as post-traumatic stress disorder, depression, and substance use disorders have significantly higher health care utilization than veterans diagnosed with mTBI alone. However, few studies of the relationship between mTBI, health care utilization, and BH conditions in the active duty military population currently exist. We examined the proportion of ADSMs with a BH diagnosis before and after a first documented mTBI and quantified outpatient utilization of the Military Health System in the year before and following injury. Materials and Methods: Retrospective analysis of 4, 901, 840 outpatient encounters for 39, 559 ADSMs with a first documented diagnosis of mTBI recorded in the Department of Defense electronic health record, subsets of who had a BH diagnosis. We examined median outpatient utilization 1 year before and 1 year after mTBI using Wilcoxon signed rank test, and the results are reported with an effect size r . Outpatient utilization is compared by BH subgroups. Results: Approximately 60% of ADSMs experience a first mTBI with no associated BH condition, but 17% of men and women are newly diagnosed with a BH condition in the year following mTBI. ADSMs with a history of a BH condition before mTBI increased their median outpatient utilization from 23 to 35 visits for men and from 32 to 42 visits for women. In previously healthy ADSMs with a new BH condition following mTBI, men more than tripled median utilization from 7 to 24 outpatient visits, and women doubled utilization from 15 to 32 outpatient visits. Conclusions: Behavioral health comorbidities affect approximately one-third of ADSMs following a first mTBI, and approximately 17% of previously healthy active duty men and women will be diagnosed with a new BH condition in the year following a first mTBI. Post-mTBI outpatient health care utilization is highly dependent on the presence or absence of BH condition and is markedly higher is ADSMs with a BH diagnosis in the year after a first documented mTBI.